COVID-19 Pandemic: A Surgical Perspective from Japan - Nepal, Pramod; Poudel, Saseem; Maharjan, Narendra (Journal of Lumbini Medical College, 2020)
Japan reported its first COVID-19 case after a returnee from Wuhan, China tested positive for the virus on 16 January, 2020. On April 8, the Japanese government declared emergency in Tokyo and six other prefectures of the country; a nationwide emergency was declared on April 16. The total reported cases were 15,477 and total deaths 755 as of May 7, 2020. Japan Surgical Society (JSS) and Japanese Society of Gastroenterological Surgery (JSGS) have published recommendations for surgery and appropriate measures of safety. Patients are triaged based on the severity of their disease and level of outbreak. The Elective Surgery Acuity Scale (ESAS) by American College of Surgeons is recommended to triage the patients. The guidelines consider the risk of infection during the interventions that generate aerosol such as tracheal intubation, extubation, tracheostomy, mask ventilation, bronchoscopy, chest drainage, gastrointestinal endoscopy etc.